Kajian Numerik dan Pemetaan Kadar Porositas Tanah pada Hutan Mangrove Gresik Menggunakan Metode Lagrange Polinomial - Muhammad Wildan; Hendrata Wibisana; Dian Purnamawati Solin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Gresik Regency, with its geographical conditions supporting the development of mangrove ecosystems, faces significant challenges due to the proximity of industrial zones, which pose potential environmental conflicts. Therefore, this research aims to map and analyze soil porosity in the Karangkiring Mangrove Forest, which plays a crucial role in maintaining ecosystem stability and supporting sustainable infrastructure planning. The methods used include collecting 16 soil samples from the field, which were then tested in the laboratory to determine porosity values. These porosity data were correlated with Landsat 8 satellite imagery through NDVI, SAVI analysis, and reflectance from bands 4 and 5. To understand the relationship between soil porosity and satellite data, a regression analysis was conducted, resulting in a quadratic polynomial equation ( y = -78.507x^2 + 49.294x - 7.0327 ), with a coefficient of determination (R²) of 0.7364, indicating a strong correlation. Based on this equation, a soil porosity distribution map was created using GIS software, which visualized the porosity distribution across the mangrove area. This map serves as an essential tool to aid decision-making related to environmental management and sustainable infrastructure planning, particularly in addressing the potential negative impacts of industrial activities on the sensitive mangrove ecosystem.